Cost-effectiveness with equity: Raising learning for marginalised girls through Camfed's programme in Tanzania - Sabates, Ricardo; Rose, Pauline; Delprato, Marcos; Alcott, Benjamin (Policy Paper No. 18/2 (REAL Centre, University of Cambridge, 2018), 2018)
This policy paper provides a cost-effectiveness analysis of Camfed’s programme in Tanzania. Camfed’s programme adopts a multidimensional approach that is aimed at reaching marginalised girls at risk of dropping out from secondary schools by using interventions that are aimed at both increasing their chances of staying in school and learning.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1247315 2339240:844SXSWR 2339240:NJNE53N8 2405685:PGA6QWXT 2405685:VQQK7F6G
Keywords: ___working_potential_duplicate; _not_EdTechHub

Resolving the “Cost-Effective but Unaffordable” Paradox: Estimating the Health Opportunity Costs of Nonmarginal Budget Impacts - Lomas, James; Claxton, Karl; Martin, Stephen; Soares, Marta (Value in Health, 2018)
Considering whether or not a proposed investment (an intervention, technology, or program of care) is affordable is really asking whether the benefits it offers are greater than its opportunity cost. To say that an investment is cost-effective but not affordable must mean that the (implicit or explicit) “threshold” used to judge cost-effectiveness does not reflect the scale and value of the opportunity costs. Existing empirical estimates of health opportunity costs are based on cross-sectional variation in expenditure and mortality outcomes by program budget categories (PBCs) and do not reflect the likely effect of nonmarginal budget impacts on health opportunity costs. The UK Department of Health regularly updates the needs-based target allocation of resources to local areas of the National Health Service (NHS), creating two subgroups of local areas (those under target allocation and those over). These data provide the opportunity to explore how the effects of changes in health care expenditure differ with available resources. We use 2008–2009 data to evaluate two econometric approaches to estimation and explore a range of criteria for accepting subgroup specific effects for differences in expenditure and outcome elasticities across the 23 PBCs. Our results indicate that health opportunity costs arising from an investment imposing net increases in expenditure are underestimated unless account is taken of likely nonmarginal effects. They also indicate the benefits (reduced health opportunity costs or increased value-based price of a technology) of being able to “smooth” these nonmarginal budget impacts by health care systems borrowing against future budgets or from manufacturers offering “mortgage” type arrangements.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jval.2017.10.006 2339240:LGRL2L6H 2405685:XZML4VWY

The True Cost of Freemium - Ferry, Anna (CPO Magazine, 2018)
Section: Data Privacy KerkoCite.ItemAlsoKnownAs: 2339240:IUSPGZNA 2405685:RR5WASM6

Moving towards cost-effective delivery models of teacher coaching: evidence from field experiments in South Africa - Kotze, Janeli; Taylor, Stephen; Fleisch, Brahm (2018)
Structured learning programmes have emerged as a promising way to address the low learning levels observed in many developing countries. The delivery model of these programmes matters, and on-site teacher coaching has been recommended to be highly effective, especially in early grade literacy. In this paper, we report on a series of government-led randomised experiments in South African primary schools that build on each other to test various models of teacher training and coaching. We find that sustained on-site coaching is more cost-effective (0.41 SD increase in test scores per USD 100) than either short coaching interventions (no significant impact) or centralized teacher training workshops (0.23 SD increase in test scores per USD 100). The ability to scale on-site coaching, however, is an open question. In the latest experiment, therefore, a virtual coaching programme was compared to on-site coaching. The focus of this paper is on the midline evaluation results from this experiment. After one year of intervention, virtual coaching was no less effective than on-site coaching at improving both the instructional practice of teachers and the targeted literacy outcomes of children. This points to the potential for technological innovations to enable wider rollout of coaching programmes, even in contexts where teachers are not familiar with new technologies.
KerkoCite.ItemAlsoKnownAs: 2339240:A58ENCQR 2339240:MC3TURVW 2405685:6RASPKEH 2405685:72SDEPAH 2405685:PLJ4WN63 2534378:4AZ7VHMD 2534378:U88KUB3W
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425920; __finaldtb; ⛔ No DOI found

Impact of Internet Access on Student Learning in Peruvian Schools - Kho, Kevin; Lakdawala, Leah; Nakasone, Eduardo (Michigan State University, Department of Economics, 2018)
We investigate the impacts of school-based internet access on pupil achievement in Peru, using a large panel of 5,903 public primary schools that gained internet connections during 2007-2014. We employ an event study approach and a trend break analysis that exploit variation in the timing of internet roll-out up to 5 years after installation. We find that internet access has a moderate, positive short-run impact on school-average standardized math scores, but importantly that this effect grows over time. We provide evidence that schools require time to adapt to internet access by hiring teachers with computer training and that this process is not immediate. These dynamics highlight the need for complementary investments to fully exploit new technological inputs and underscores the importance of using an extended evaluation window to allow the effects of school-based internet on learning to materialize.
Publication Title: Working Papers KerkoCite.ItemAlsoKnownAs: 2339240:7URC6DBK 2405685:SHDUYVBY
Keywords: Education; ICT; Internet; Schooling

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10833-018-9325-4 10/gf6298 2339240:3W37ZTWQ 2405685:ME5VHAM9
Keywords: ___working_potential_duplicate

Through the looking glass: can classroom observation and coaching improve teacher performance in Brazil? - Bruns, Barbara; Costa, Leandro; Cunha, Nina (Economics of Education Review, 2018)
We conducted a randomized evaluation of a program in Brazil that provided secondary schools with classroom observation feedback and access to expert coaching. Coaching content was based on Teach Like A Champion, by Douglas Lemov, which imparts practical strategies to increase teachers’ effectiveness by maximizing time on instruction and student engagement. In treatment schools, the program raised the skills of pedagogical coordinators tasked with supporting teachers to improve instruction, increased teachers’ time on instruction, raised student engagement and produced statistically significant student learning gains. Program schools performed 0.05–0.09 SD higher in 10th grade math and Portuguese on a state test and 0.06 SD higher in Portuguese on a national high school leaving test (12th grade). High quality coaching delivered to the coordinators via Skype kept costs at $2.40 per student, making the program a cost-effective and promising strategy for school-based efforts to raise teachers’ classroom effectiveness. (I21, I25, I28, J18, O15)
Extra URL: http://www.sciencedirect.com/science/article/pii/S0272775717303576 KerkoCite.ItemAlsoKnownAs: 10.1016/j.econedurev.2018.03.003 10/ggft3x 2129771:PXEQ493U 2339240:EJ9DHWVT 2339240:TJCEV7VS 2405685:27VSFIJU 2405685:7A2ZCMGH 2405685:PH86GT2T 2534378:CH4WAJDT 2534378:FM4VRQ7G 2534378:X3NNFD6B
Keywords: Classroom observation; Economic development; Economic impact; Educational economics; Randomization; Teacher coaching; __:import:01; __:match:final; __:matched; __:study_id:2425900; ___working_potential_duplicate; __finaldtb

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Publisher: Horizon Research Publishing KerkoCite.ItemAlsoKnownAs: 10.13189/ujer.2018.060604 10/gf622k 2339240:FWBVWVA2 2405685:ARBG7E6A
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

Impact of Education on Labour Market Outcomes in Rural and Urban India - Pradhan, K. C.; Parida, P. C.; Sarangi, Tapas (Reflecting on India’s Development: Employment, Skill and Health, 2018)
This paper examines the returns to education with respect to three labour market outcomes namely wages, employment and occupation using the National Sample Survey Office (NSSO) 68th round (2011–12) data. Wage equation (without selection bias) results point to the fact that returns to education increase at an increasing rate as the level of education increases and the impact of education is found relatively higher in the case of urban than rural areas. In case of employment, the study finds that compared to illiterates, the chances of higher educated people going to agriculture sector is less. This is true even in the case of rural areas whereas the interactive variable (education with rural dummy) is found negatively associated with employment in agriculture sector. Occupation results suggest that there is a strong association between higher education (under graduate and graduate and above) with professional occupations and less with agriculture and fishery and unskilled occupations, suggesting the need for improving education and creating quality employment opportunities in the rural areas that may help in arresting the growing urban burden.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-13-1414-8_8 2339240:22I8PCDJ 2405685:8FWZU7FX
Keywords: Education; Employment; India; Occupation; Urban-rural gap; Wages

The difference between economic and financial analysis for WASH services - Ross, Ian (WASHeconomics.com, 2018)
The distinction between economic analysis and financial analysis is not always straightforward. In this post I try to clarify this. Definitions I have previously defined WASH economics as “the stud…
KerkoCite.ItemAlsoKnownAs: 2339240:RI9C4FHT 2405685:QWR4ZRBS

Global Dataset on Education Quality : A Review and Update (2000-2017) - Patrinos, Harry Anthony; Angrist, Noam (World Bank Group, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:IB5T4GSH 2405685:MCNGDVIH

Learning-Adjusted Years of Schooling (LAYS): Defining A New Macro Measure of Education - Filmer, Deon; Rogers, Halsey; Angrist, Noam; Sabarwal, Shwetlena (World Bank, 2018)
KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8591 2339240:3A9F6FVB 2339240:KGVQPHCJ 2405685:59ERQXRR 2405685:GSG23QSA 2405685:TP9IZVSC 2447227:6BFXZ6TA 2561267:ELKQGNZN
Keywords: _B:important; ___working_potential_duplicate; _final_bib; _important; _s:DFID; ⛔ No DOI found; ❓ Multiple DOI

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

World Development Report 2018: Learning to realize education’s promise - World Bank (World Bank Group, 2018)
World Development Report 2018: LEARNING to Realize Education’s Promise
KerkoCite.ItemAlsoKnownAs: 10.1596/978-1-4648-1096-1 2339240:5YCGPE5H 2339240:7URY7SPB 2339240:BFKFTEHP 2339240:HZL7FCFK 2339240:VYNPXJB6 2339240:YM6MIDK7 2405685:7JNTDBCR 2405685:8K4QNUT8 2405685:BF2ZWSJV 2405685:GAYWXIDL 2405685:HQFK65IQ 2405685:HUESCDK5 2405685:JL8R2527 2405685:PZI834WE 2534378:BKV4NR6U
Keywords: C:Low- and middle-income countries

Nudging in education - Damgaard, Mette Trier; Nielsen, Helena Skyt (Economics of Education Review, 2018)
Can we nudge children, adolescents and their parents to make better decisions on education? And can we nudge teachers to support and encourage better decision making? Education decisions are taken at young ages and involve immediate costs and potential, future benefits. In such settings behavioural barriers (e.g. lack of self-control, limited attention and social norms) likely influence choices and this may motivate the use of low cost ‘nudges’ to gently push behaviour in the desired direction. Our review of nudging interventions shows that while nudging often has positive effects, the greatest effects often arise for individuals affected most by the behavioural barrier targeted by the intervention. Hence understanding underlying behavioural mechanisms is crucial. Negative effects may arise in situations where nudges potentially crowd-out intrinsic motivation, if nudges pressurise individuals, or in situations where the choice architect has an insufficient understanding of behavioural mechanisms.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.econedurev.2018.03.008 2339240:YBXW7W6Z 2405685:TFBCJC4T
Keywords: Behavioural bias; Boost policies; Human capital investment

Inputs, Incentives, and Complementarities in Education: Experimental Evidence from Tanzania - Mbiti, Isaac; Muralidharan, Karthik; Romero, Mauricio; Schipper, Youdi; Manda, Constantine; Rajani, Rakesh (National Bureau of Economic Research, 2018)
We present results from a large-scale randomized experiment across 350 schools in Tanzania that studied the impact of providing schools with (a) unconditional grants, (b) teacher incentives based on student performance, and (c) both of the above. After two years, we find (a) no impact on student test scores from providing school grants, (b) some evidence of positive effects from teacher incentives, and (c) significant positive effects from providing both programs. Most importantly, we find strong evidence of complementarities between the two programs, with the effect of joint provision being significantly greater than the sum of the individual effects. Our results suggest that combining spending on school inputs (which is the default policy) with improved teacher incentives could substantially increase the cost-effectiveness of public spending on education.
Series: Working Paper Series KerkoCite.ItemAlsoKnownAs: 10.3386/w24876 2339240:6KRPH6ZG 2405685:N3H3SZ7C 4656463:DX4NAZF7

Identifying the essential ingredients to literacy and numeracy improvement: Teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Simmons Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Several rigorously evaluated programs have recently shown positive effects on early literacy and numeracy outcomes in developing countries. However, these programs have not been designed to evaluate which ingredients of the interventions are most essential to improve literacy outcomes. Policy makers therefore lack evidence as to whether program ingredients such as teacher professional development (PD), instructional coaching, learner materials, teachers’ guides, community support, or technology are required for program impact. The Kenya Primary Math and Reading Initiative was a randomized controlled trial that compared three treatment groups with speciﬁc ingredients and a control group. Using literacy and numeracy outcome measures for grades 1 and 2, we evaluated the beneﬁts of the following ingredients: (1) teacher PD and teacher instructional support and coaching; (2) revised student books in literacy and numeracy, at a 1:1 ratio, added to PD and instructional support; and (3) structured teacher lesson plans added to student books, PD, and instructional support. We found that two of the three combinations of ingredients had statistically signiﬁcant positive impacts on learning outcomes. The results showed that the third combination—PD, teacher instructional support and coaching, 1:1 student books, and structured teacher lesson plans—was most effective. A cost-effectiveness analysis on the ingredients showed that the option of PD and instructional support, 1:1 revised books, and teachers’ guides was the most expensive, but that the additional impact on learning made this the most cost-effective intervention. This study rigorously analyzes which ingredients for literacy and numeracy improvement would be most effective for overall impact, and suggests to policy makers that careful decisions regarding program ingredients will lead to more effectively designed and implemented interventions to improve learning in developing countries.
EdTechHub.Copy: 2129771:3IIW96ZB shortDOI: 10/gftrqf KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2018.01.018 10/gftrqf 2129771:3IIW96ZB 2339240:AUEREUTT 2339240:NNWXI67C 2339240:QWI89XDJ 2339240:X37484JK 2405685:37II7RPP 2405685:4PBTS4CP 2405685:5LADY8ET 2405685:L36BGXMK 2405685:PT6BTPEC
Keywords: Africa; C:Kenya; Literacy; Numeracy; Program Evaluation; Program evaluation; Quantitative; Randomized controlled trial; Reading; Teacher Professional Development; ___working_potential_duplicate; numeracy; randomized control trial

Impact of Online Computer Assisted Learning on Education: Evidence from a Randomized Controlled Trial in China - Bai, Yu; Tang, Bin; Wang, Boya; Auden, Emma; Mandell, Blake (Stanford University, 2018)
Education of poor and disadvantaged populations has been a long-standing challenge for education systems in both developed and developing countries. In China, millions of students in rural areas and migrant communities lag far behind their urban counterparts in terms of academic achievement. When they fall behind, they often have no way to catch up. Many of their parents have neither the skills nor the money to provide remedial tutoring; rural teachers often do not have time to give students the individual attention they need. Given this, there is growing interest by both educators and policymakers in helping underperforming students catch up using computer assisted learning (CAL). While CAL interventions have been shown to be effective internationally and elsewhere in China, traditional software-based CAL programs are difficult and costly to implement. An online version of CAL (OCAL), however, may be able to bypass many of offline CAL’s implementation problems and enhance the remedial tutoring experience. Unfortunately, there is little empirical evidence on whether OCAL programs can be effective in improving the quality of rural primary school education in developing countries. The objective of this paper is to examine the impact of an OCAL intervention on the academic and non-academic performance of students and to explore the mechanism behind OCAL’s impact. Importantly, we also aim to assess the cost effectiveness of the new OCAL program versus traditional CAL interventions. To achieve these objectives, we carried out a randomized controlled trial (RCT) involving over 1650 fifth grade students in 44 schools in rural areas and migrant communities across China. Students in the 22 treatment schools attended two 40minute OCAL sessions during their computer class each week for one semester; the students in the other 22 schools were in the control group and did not receive any intervention. According to our findings, OCAL improved overall English scores of students in the treatment group relative to the control group by 0.56 standard deviations. This impact is large when compared with offline CAL programs. We found that OCAL also led to a positive change in the attitudes of students towards English learning and towards student aspirations for their future education level. We found three possible explanations for OCAL’s impact. After rejecting the possibility of the Hawthorne Effect or self-efficacy-induced changes, we believe interest-oriented stimulation is the main source of improvement among students. The chance for comparison and competition with peers, as well as customized remedial question banks tailored to each student’s individual needs, likely contributed to the measured increases in academic performance among students in our sample. Cost-effectiveness analysis showed that the OCAL program is more cost-effective than traditional offline CAL, a comparison which is significant for policymakers as it indicates high potential for OCAL program expansion.
KerkoCite.ItemAlsoKnownAs: 2339240:UVG9KSAI 2339240:ZLVS7CVZ 2405685:7L744UX5 2405685:HM587PSY
Keywords: Quality: H; Relevance: M; ⛔ No DOI found

MOOCs for Teacher Professional Development: Reflections and Suggested Actions - Misra, Pradeep Kumar (Open Praxis, 2018)
Teacher Professional Development (TPD) has become a major policy priority within education systems worldwide. But keeping teachers professionally up-to-date and providing them professional development opportunities on continuing basis is a big challenge. Massive Open Online Courses (MOOCs) can be a cost and resource effective means to complement the traditional methods of professional development of teachers. This optimism is based on the assumption that use of MOOCs will facilitate mass training of teachers as per their convenience and ease. The other assumption is that being MOOCs-based training, it will be easy to adapt it to different cultures and languages. Considering these assumptions, this concept paper which is based on reviews of different reports, documents and research papers - discusses the challenges of TPD, reflects upon promises of using MOOCs for TPD; details initiatives and experiences of using MOOCs for TPD; and suggests actions for promoting the use of MOOCs for TPD.
KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.10.1.780 2339240:27J8DKI6 2405685:AYFYMSM8

EdTech for Learning in Emergencies and Displaced Settings: A rigorous review and narrative synthesis - Tauson, Michaelle; Stannard, Luke (Save The Children, 2018)
Globally, according to UNESCO (2017), 264 million children of primary and secondary school age are out school. UNESCO also estimates that worldwide roughly 100 million young people are fully illiterate. While data on attendance, enrolment, and literacy can be difficult to gather in fragile and conflict-affected settings, estimates suggest that children in these settings are roughly three times more likely to be out of school than children living in stable, but low-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:39QITWJZ 2339240:6F23G9BX 2339240:CX7MJW5R 2339240:D26Y5JXH 2339240:FBAM53IG 2339240:FBCFVAEE 2339240:FHZXSRXI 2339240:G8GRKFFX 2339240:KL87UZMA 2339240:NRUBXTAT 2339240:RHDU25IK 2339240:SLJGQQ9G 2405685:28WH3URF 2405685:2YFK36CZ 2405685:6QS8CQ9G 2405685:9QNHP33B 2405685:9ZFQ6L5J 2405685:CMAMJWTI 2405685:H2SWIIEB 2405685:JJQTKVY2 2405685:KETBQUYZ 2405685:KLHB3S5G 2405685:NSWYZQA7 2405685:PF7AX4UZ 2405685:X2N4NZRQ 2405685:YG9HXGM8 2534378:WMLTBU37
Keywords: GENERAL - to be categorised; Google Scholar/ forced displacement edtech; IMPORT_FROM_DFID_RITE; Important; Read; _THEME: Teacher Professional Development; ___working_potential_duplicate; auto_merged; ⛔ No INSPIRE recid found

An Overview of ICT for Education of Refugees and IDPs - Joynes, Chris; James, Zoe (K4D, Knowledge, Evidence, and Learning for Development, 2018)
This rapid review examined examples of ICT approaches to address the education needs of those living in IDP and refugee camps and lessons learned from these experiences. Although ICT is considered a good system to fulfil the education needs within refugee settings, many studies conclude that access to ICTs in schools or at home is not sufficient to improve learning outcomes. It is due to the role of a mentor or tutor figure is seen as key to productive learner engagement with technology, and the effectiveness of ICT-based education is reliant on appropriate teacher training to ensure successful up-take at the classroom level (Tauson & Stannard 2018: 47, 62; UNESCO 2018: 74; Carlson 2013: 30). Secondly, in terms of content, ICTs for education should provide content that is responsive or adaptable to the learners’ level, is implemented in line with the local curriculum and also is relevant to the learners’ context (Tauson & Stannard 2018: 36-38, 61). Despite this potential for ICTs, there remains a broad lack of evidence related to education in refugee settings (Burde et al. 2015; Tauson & Stannard 2018; World Bank 2016). In particular, more information is needed on pedagogic design, on the effective use of ICTs for learning, on the role of ICTs in ensuring continuity of and linkages between learning in formal and non-formal settings, on the role of ICTs in educational data-gathering, and on the cost-effectiveness of ICT-led interventions (Burde et al 2015; Tausin & Stannard 2018; Carlson 2013). In light of the availability of evidence, some of the studies cited here instead supplement their findings by drawing on observational studies, and on studies on effective ICT usage from learners in non-refugee contexts (Burde et al. 2015; Tauson & Stannard 2018).
KerkoCite.ItemAlsoKnownAs: 2339240:75ZRE2RA 2339240:J9VYGNUA 2339240:N4VI3AHC 2405685:3Z2JBF58 2405685:UUEEVW9Z 2405685:VSQUMYUI
Keywords: Google Scholar/ "education technology" refugees; RER theme_general; RER theme_pedagogies and modalities; ⛔ No DOI found

Social media use by undergraduate students of education in Nigeria: a survey - Wickramanayake, Lalith; Muhammad Jika, Saidu (The Electronic Library, 2018)
Purpose This paper aims to investigate teacher students’ perceptions, intentions, experiences, attitudes, opinions and barriers concerning social media use and impact of social media on their learning process. Design/methodology/approach A stratified sampling technique was applied to draw the sample, and 242 teacher students were selected as a sample from three higher educational institutions in Gombe State, Nigeria. A questionnaire survey method was used to collect the data. Data analysis was by means of simple and inferential statistics. Findings The students widely used mobile phones to access social media, and social media was extremely popular for education, entertainment and communication among them. Educational and informational communities were also preferred by students to other social media communities. The study further revealed that effective social media usage among students enhanced their different types of skills including learning. Unstable electricity connections, security and privacy issues, internet costs and unreliable internet connections were recorded as some barriers concerning students’ social media use. Originality/value The outcome of this study will be a unique contribution because the pertinent literature provides little evidence or research highlights concerning teacher students’ social media use. Even more, the results of the present study may be a useful resource for university administrators, education policymakers and innovative teachers in universities – especially in developing countries and particularly Nigeria – when considering integration of modern techniques and technologies with university teaching and learning.
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/EL-01-2017-0023 2339240:AGAUINHT 2405685:PISZZ6ZX
Keywords: Internet-based learning; Media-based teaching; Nigeria; Social media; Teaching students; User studies

Growth prospects, market challenges and policy measures: Evolution of mobile broadband in Pakistan - Hanif, Muhammad Shehzad; Yunfei, Shao; Hanif, Muhammad Imran (Digital Policy, Regulation and Governance, 2018)
Purpose The paper aims to explore the long-term prospects of mobile broadband adoption in a developing country. The supply-side and demand-side policy measures are recommended to counter the challenges to broadband adoption. Design/methodology/approach Methodologically, this study uses document analysis to explain secondary data including growth statistics, trade literature and previous scholarly research. Based on the growth statistics of broadband and the informed market insights, the research discusses the prevailing market threats and recommends counter measures to improve the long-term prospects of broadband propagation. Findings The growth of mobile broadband is settling down in Pakistan due to various barriers like cost, literacy, security and unavailability of local content. Collaborative efforts are required by the government, the service providers and the people to enhance the adoption of broadband service and secure economic benefits of the broadband. Practical implications The research offers useful implications for managers and policymakers in Asian and African developing countries; the policy measures discussed here may serve as guidelines for them in the design of their own policies regarding broadband supply and demand. Originality/value The study makes an effort to examine the broadband growth in a developing country on the basis of both quantitative and qualitative aspects. The research endeavors to fill the gap on the particular scholarship of research covering potential uptake of broadband services and the effects of constraining elements to broadband adoption in a developing country.
KerkoCite.ItemAlsoKnownAs: 10.1108/DPRG-04-2017-0014 2339240:SGX3L6KS 2405685:5KV4NF9R

Short message service (SMS)–based remote support and teacher retention of training gains in Malawi - Slade, Timothy S.; Kipp, Scott; Cummings, Stirling; Nyirongo, Kondwani (Cultivating dynamic educators: case studies in teacher behavior change in Africa and Asia, 2018)
This book responds to growing recognition by international education professionals, policy makers, and funding partners of the need for qualified teachers and interest in the subject of teacher professional development (also referred to as "teacher behavior change"). The book responds to important questions that are fundamental to improving teaching quality by influencing teaching practice. These questions include: How do we provide high-quality training at scale? How do we ensure that training transfers to change in practice? What methods are most cost-effective? How do we know what works? The book includes case studies describing different approaches to teacher behavior change and illustrates how specific implementation choices were made for each context. Individual chapters document lessons learned as well as methodologies used for discerning lessons. The key conclusion is that no single effort is enough on its own; teacher behavior change requires a system-wide view and concerted, coordinated inputs from a range of stakeholders. This book contains the following chapters: (1) Understanding and Influencing Teacher Behavior Change: Editorial Introduction (Sarah Pouezevara); (2) Changing Teacher Educators' Conceptions and Practices Around Literacy Instruction: Lessons from Teacher Educators' Professional Development Experiences in Ethiopia (Dawit Mekonnen, Marion Fesmire, Adrienne Barnes, Stephen Backman, and Flavia Ramos-Mattoussi); (3) School Leadership and Early Grade Reading: Examining the Evidence in Zambia (Mitchell Rakusin and Guy Bostock); (4) Making Sense of Teacher In-Service Training in the Philippines (Nancy Clark-Chiarelli and Bonita Cabiles); (5) Short Message Service (SMS)-Based Remote Support and Teacher Retention of Training Gains in Malawi (Timothy S. Slade, Scott Kipp, Stirling Cummings, and Kondwani Nyirongo); (6) Relationships Between Coach Support and Teachers' Adoption of New Instructional Practices: Findings from the Nigeria Reading and Access Research Activity (RARA) (Karon Harden, Alison Pflepsen, and Simon King); (7) Using Activity Theory to Understand Teacher Peer Learning in Indonesia (Sarah Pouezevara, Feiny Sentosa, and Tifa Asrianti); (8) Teacher Motivation and Behavior Change: Results of the Teacher Motivation Diagnostic Tool in Northern India (Molly Hamm-RodrÃguez, Emily Richardson, and Jarret Guajardo); and (9) Once More Up the Mountain: The Promise of High-Quality Teaching Depends on Behavior Change (Lee E. Nordstrum). Contains a section about the contributors and an index. (Individual chapters contain references.) [Erin Newton compiled this volume.]
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2339240:2M2HXSJN 2405685:SNDDADWB 2405685:SNTV94NA 2534378:7FFHYISA 2534378:ASX6DAFV 2534378:WH9M9DZM
Keywords: __:import:02; __:match:final; __:matched; __:study_id:3123693; __finaldtb; ⛔ No DOI found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode